30 Exploring opinions about research translation held by leading australian stroke researchers. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Lynch, Elizabeth; Ramanathan, Shanthi; Middleton, Sandy; Bernhardt, Julie; Nilsson, Michael; Cadilhac, Dominique
Abstract : Objectives: There is a growing need for researchers to demonstrate impact, which is closely linked with research translation. In Australia, the National Health and Medical Research Council funded a Centre of Research Excellence in Stroke Rehabilitation and Brain Recovery (CRE-Stroke) from 2015–2019 to enhance collaborations between researchers conducting different types of stroke rehabilitation research. CRE-Stroke has 5 research streams: Basic Science, Imaging Discovery, Clinical Trials, Implementation Science and Data Linkage. In order to guide strategies to boost research translation and impact, in 2016 researchers within the Implementation Science stream of CRE-Stroke sought to explore opinions held by researchers conducting pre-clinical and clinical stroke rehabilitation research about research translation. Method: A mixed methods (explanatory sequential) study design was used, comprising a paper-based survey and semi-structured interviews. A convenience sample of researchers attending a CRE-Stroke Rehabilitation Workshop and Annual Scientific Meeting of the host organisation were invited to complete the survey. Researchers were asked to describe research translation, discuss who should be responsible to oversee research translation, and whether researchers believe they have the knowledge and skills to translate their research. Survey data from 57 participants were analysed descriptively and were used to inform development of the interview guide. Twenty-seven researchers were purposively selected to provide representation of the breadth of research studies being conducted within CRE-Stroke and were invited to participate in semi-structured interviews; 22 interviews were conducted. Interviews were audio-recorded and transcribed, checked for accuracy by participants, and data were thematically analysed by two reviewers. Results: Research translation was described two ways: translating to other research and translating to clinical practice and policy. Most researchers (XX%) perceived they were responsible for translating their research via publication, and for 80% of survey participants, publication signalled a project's completion. Some interview participants reinforced the view that the research team's responsibility for translation ceased when results were published or incorporated into guidelines; others believed that researchers should ensure their findings were used in clinical practice, either independently or through collaborating with clinicians and implementation experts. Only 35% of the survey respondents reported having the skills and knowledge to translate their research beyond the narrow remit of publications and conference presentations. Researchers consistently stressed the difficulty and complexity of research-to-practice translation, and most felt inadequately skilled to coordinate clinical translation projects. In contrast, researchers' self-reported lack of translation skills did not appear to adversely influence translation to other research projects. Conclusions: Researchers consistently assume responsibility for disseminating their results via publications and conference presentations, and express confidence to translate their research findings to other research. However, translating to clinical practice is less straightforward, both in terms of required skills and lines of responsibility, because in Australia, no group has a clear mandate to ensure that research is translated to clinical practice. To support research translation within CRE-Stroke, a research translation template has been introduced and its use will be evaluated. CRE-Stroke also provides financial support for collaborative projects between researchers and clinicians to boost research and translation capacity.